Intravascular T-cell lymphoma in a patas monkey (Erythrocebus patas) - Lampe, Karen (Primate Biol, 2017)
A 9-year-old female captive patas monkey (Erythrocebus patas) presented with poor general condition, inability to stand, petechiae, anaemia, thrombocytopenia, and leukocytosis. Due to poor response to treatment, the animal was euthanized 16 days later. Postmortem examination revealed hemorrhages in several organs and bilateral cerebral infarctions. Histologically, prominent accumulations of large neoplastic lymphocytes in cerebral and meningeal blood vessels were demonstrated within the lesions and in other organs (e.g., bone marrow, ovary, intestine). Immunohistochemically, neoplastic cells expressed CD3 and Ki-67. PCR revealed a lymphocryptovirus (LCV) infection, while Epstein–Barr nuclear antigen 2 (EBNA2) could not be demonstrated within neoplastic cells by means of immunohistochemistry. Based on the pathological findings, an intravascular lymphoma (IVL) of T-cell origin was diagnosed. To the authors' knowledge, this is the first report on this rare entity in a nonhuman primate.